A Dose-escalation Study of Recombinant Human Interleukin-18 in Combination With Ofatumumab After Autologous Peripheral Blood Stem Cell Transplantation for Lymphoma. Issue 3 (April 2018) - Robertson, Michael J.; Stamatkin, Christopher W.; Pelloso, David; Weisenbach, Jill; Prasad, Nagendra K.; Safa, Ahmad R.
Abstract : Interleukin-18 (IL-18) is an immunostimulatory cytokine that augments antibody-dependent cellular cytotoxicity mediated by human natural killer cells against antibody-coated lymphoma cells in vitro and that has antitumor activity in animal models. Ofatumumab is a CD20 monoclonal antibody with activity against human B-cell lymphomas. A phase I study of recombinant human (rh) IL-18 given with ofatumumab was undertaken in patients with CD20 + lymphoma who had undergone high-dose chemotherapy and autologous peripheral blood stem cell transplantation. Cohorts of 3 patients were given intravenous infusions of ofatumumab 1000 mg weekly for 4 weeks with escalating doses of rhIL-18 as a intravenous infusion weekly for 8 consecutive weeks. Nine male patients with CD20 + lymphomas were given ofatumumab in combination with rhIL-18 at doses of 3, 10, and 30 μg/kg. No unexpected or dose-limiting toxicities were observed. The mean reduction from predose levels in the number of peripheral blood natural killer cells after the first rhIL-18 infusion was 91%, 96%, and 97% for the 3, 10, and 30 μg/kg cohorts, respectively. Serum concentrations of interferon-γ and chemokines transiently increased following IL-18 dosing. rhIL-18 can be given in biologically active doses by weekly infusions in combination with ofatumumab after peripheral blood stem cell transplantation to patients with lymphoma. A maximum tolerated dose of rhIL-18 plus ofatumumab was not determined. Further studies of rhIL-18 and CD20 monoclonal antibodies in B-cell malignancies are warranted.